2011
DOI: 10.1111/j.1466-7657.2011.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety: nursing students' perspectives and the role of nursing education to provide safe care

Abstract: VAISMORADI M., SALSALI M. & MARCK P. (2011) Patient safety: nursing students' perspectives and the role of nursing education to provide safe care. International Nursing Review58, 434–442 Background and Aim:  Nurses as the largest group of healthcare providers are in the best position to improve patient safety. In preparing future nurses, nurse educators have an important role in developing the knowledge, skills and attitudes among nursing students related to patient safety. The aim of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 40 publications
3
100
1
14
Order By: Relevance
“…There was consensus that patient protection is fundamental to preserving clinical safety. This finding supports previous research that identified holistic patient well-being as central to undergraduate students' perspectives about safety [12,28] . The findings of this study also characterized unsafe clinical milieus by the absence of an overt focus on safety, appropriate professional development, and engaged competent educators.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There was consensus that patient protection is fundamental to preserving clinical safety. This finding supports previous research that identified holistic patient well-being as central to undergraduate students' perspectives about safety [12,28] . The findings of this study also characterized unsafe clinical milieus by the absence of an overt focus on safety, appropriate professional development, and engaged competent educators.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, students with greater theoretical knowledge had higher clinical knowledge and skills compared to those students who had limited theoretical exposure. They agree with the premise of students need time in transitioning knowledge for safe 'deliberate, conscientious practice' [12] . Time offer opportunities for novice learners to engage in critical dialogue with educators about patient safety as lived.…”
Section: Learning Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty one teaching contact hours are allocated to pharmacology in 4 years. Therefore, nursing students often graduate without meaningful or practical knowledge of patient safety (Vaismoradi et al, 2011).…”
Section: Settings and Participantsmentioning
confidence: 99%
“…As the product of nurses' shared values and beliefs, medication safety can be taught, developed and internalised in undergraduate nursing programmes (Butterworth et al, 2011) to transform safety culture (Reid and Catchpole, 2011;Vaismoradi et al, 2011).…”
Section: Nurse Education and Medication Errorsmentioning
confidence: 99%